Early Improvement of Neuropsychological Impairments During Detoxification in Patients with Alcohol Use Disorder. (11th October 2022) - Angerville, Bernard; Ritz, Ludivine; Pitel, Anne-Lise; Beaunieux, Hélène; Houchi, Hakim; Martinetti, Margaret P; Naassila, Mickaël; Dervaux, Alain
Abstract: Aims: To assess recovery of alcohol-related neuropsychological deficits in a group of patients with pure severe alcohol use disorder (AUD) during a detoxification program using the Brief Evaluation of Alcohol-Related Neuropsychological Impairment (BEARNI) test. Methods: Thirty-two patients with severe AUD using DSM-IV criteria (24 men, mean age = 45.5 ± 6.8 years old) were assessed using the BEARNI 8 ± 2 days after alcohol cessation (T1) and then were reassessed within 18 ± 2 days after alcohol cessation (T2). The primary study endpoint was the number of patients initially impaired at T1 who recovered cognitive functions at T2 assessment. Results: At T1, 59% (n = 19) patients with pure severe AUD had at least one impaired cognitive function assessed by the BEARNI. At T2, 63% of the patients with AUD with deficits at T1 had normal BEARNI cognitive scores (χ 2 = 7.7, P = 0.005); specifically, the percentages of participants with normal subtest scores were 63% on memory (χ 2 = 12.4, P = 0.0004), 100% on verbal fluency (χ 2 = 16; P = <0.0001), 60% on alphabetical span (χ 2 = 12.8; P = 0.0003) and 67% on visuospatial (χ 2 = 15, P = 0.0001). Conclusions: The cognitive impairments of two-thirds of patients with pure AUD included in the present study recovered within 18 days of abstinence, earlier than reported in previous studies. Abstract : Short Summary: A 3-week period of sobriety allows significant neuropsychological recovery in two-thirds of patient with pure AUD.